2012
DOI: 10.5194/aab-55-132-2012
|View full text |Cite
|
Sign up to set email alerts
|

Milk quality, manufacturing properties and blood biochemical profile from dairy cows fed peas (<i>Pisum sativum</i> L.) as dietary protein supplement

Abstract: Pea (Pisum sativum L.), a protein-rich legume seed well adapted to many climatic areas and widely used for feed and food, was fed to Italian Friesian breed cows for 16 weeks to assess its effects on milk yield and production, renneting properties and metabolic responses. Cows within each group were assigned to two isonitrogenous and isoenergetic concentrates based on corn plus soybean meal or peas. Individual milk samples were collected from two consecutive milkings, composited, and then analysed for fat, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…This was due to a decreased degradability of pea protein leading to a decreased ammonia level in the rumen and urea level in blood. Similar results were obtained with dairy cows (Tufarelli et al, 2012). Facciolongo et al (2014), by replacing soybean meal with peas in feed mixture for lambs, also found a decrease in blood urea, but the differences were not significant (15.84 to 14.29 mg dL −1 ).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…This was due to a decreased degradability of pea protein leading to a decreased ammonia level in the rumen and urea level in blood. Similar results were obtained with dairy cows (Tufarelli et al, 2012). Facciolongo et al (2014), by replacing soybean meal with peas in feed mixture for lambs, also found a decrease in blood urea, but the differences were not significant (15.84 to 14.29 mg dL −1 ).…”
Section: Resultssupporting
confidence: 69%
“…Due to the increasing pollution of soy with mould and mycotoxins, and due to the fact that significant amounts of soy are of GMO origin (Bonanno et al, 2012), which is prohibited in organic farming (European Union, 2007), alternative solutions are being sought. As a successful alternative in organic ruminant production, peas can be used (Tufarelli et al, 2012;Antunović et al, 2013Antunović et al, , 2016. Giger-Reverdin et al (2015) pointed out that pea seeds can be a relevant Z.…”
Section: Introductionmentioning
confidence: 99%
“…Pea (Pisum sativum) is considered as a potential feed ingredient in diets of pigs (Stein et al, 2006) and poultry (Nalle et al, 2011). Moreover, peas contain high amounts of protein and energy, and their amino acid content is similar to that of soybean (Fru-Nji et al, 2007;Tufarelli et al, 2012). The inclusion of a high amount of raw peas in diets has been reported to have a detrimental effect on the performance of broilers and laying hens (Igbasan and Guenter, 1997;Diaz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Partial replacement of SBM with SFC reduced the concentration of total protein, globulin, AST, and GGT enzymes and increased BHB blood concentration, while no significant differences in biochemical blood parameters were found when replacing SBM with P. Interaction between diet and stage of lactation influenced the concentration of glucose, urea, albumin, cholesterol, NEFA, BHB, globulin, as well as activity of ALT and ALP. Tufarelli et al (2012) reported that cows fed diets in which SBM was replaced by pea grains had reduced blood and milk urea concentrations, which almost certainly occurred because of decreased degradability of pea protein leading to the decreased ammonia level in the rumen and urea level in milk and blood. In general, changes in urea concentration are correlated with the content of ruminal ammonia, which depends on the metabolic activity of ruminal microorganisms that transform ammonia nitrogen into a bacterial protein, a process that requires energy (Gonzaga Neto et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned could be related to higher content of crude protein in diet of ewes with the addition of SFC (Table 1). Tufarelli et al (2012) also determined the increase of BHB concentration in blood of cows fed diet with addition of peas compared with SBM, although without significant differences. When feeding lactating cows diets in which soybean meal was replaced with peas, Petit et al (1997) did not find significant differences in the urea concentration, total protein, and NEFA in the blood.…”
Section: Discussionmentioning
confidence: 99%